Occupational exposures and sarcoidosis: current understanding and knowledge gaps. Issue 2 (March 2022) - Lin, Nancy W.; Maier, Lisa A.
Abstract : Purpose of review: Sarcoidosis is an idiopathic granulomatous disease that primarily affects the lungs. Several lines of evidence suggest that occupational exposures are associated with disease risk. This review critically evaluates studies using the Bradford Hill criteria for causation to determine if a causal relationship can be established between occupational exposure and sarcoidosis. Recent findings: Large epidemiological studies have proposed multiple occupational exposures associated with sarcoidosis but lack consistency of results. Many convincing studies demonstrate an association between World Trade Center (WTC) dust and sarcoidosis, which illustrates a causal relationship based on the fulfillment of the Bradford Hill criteria. Studies describing an association between silica/metals and sarcoidosis are intriguing but fulfill a limited number of the Bradford Hill criteria and warrant further investigation before a causal relationship can be determined. Finally, we also discuss preliminary studies associating sarcoidosis phenotypes with specific occupational exposures. Summary: Using the Bradford Hill criteria for causation, we demonstrate that WTC dust has a causative relationship with sarcoidosis, which reinforces the theory that sarcoidosis is an exposure-related disease. More research is needed to determine other specific occupational exposures causing disease.